Binding of NF-Y to transposable elements in mouse and human cells - Mirko Ronzio; Andrea Bernardini; Alberto Gallo; Roberto Mantovani; Diletta Dolfini (Mobile DNA)
Abstract Background Transposable Elements (TEs) represent a sizeable amount of mammalian genomes, providing regulatory sequences involved in shaping gene expression patterns. NF-Y is a Transcription factor -TF- trimer that binds to the CCAAT box, belonging to a selected group implicated in determining initiation of coding and noncoding RNAs. Results We focus on NF-Y TE locations in 8 human and 8 mouse cells. Binding is exclusive for retroviral LTR12, MLT1 and MER in human and RLTR10 and IAPLTR in mouse cells. Cobinding and analysis of the DNA matrices signal enrichment of distinct TFs neighboring CCAAT in the three TE classes: MAFK/F/G in LTR12 and USF1/2 in MLT1 with precise alignment of sites, PKNOX1, MEIS2, PBX2/3 TALE TFs in MER57. The presence of “epigenetic” marks in human cells indicate prevalent co-association with open chromatin in MER, closed in LTR12 and mixed in MLT1. Based on chromatin features, these locations are mostly marked as enhancers, as confirmed by analysis of loci predicted to generate eRNAs. Conclusions These results are discussed in the context of functional data, suggesting a complex -positive and potentially-negative role of NF-Y on distinct classes of repetitive sequences.